Exposed epitopes on a Trypanosoma equiperdum variant surface glycoprotein altered by point mutations. - Baltz, T (1991)
African trypanosomes are covered by a dense protein layer that is immunologically distinct on different trypanosome isolates and is termed the variant surface glycoprotein (VSG). The different VSGs are expressed in a general order, where some VSGs appear preferentially early in infection and others only later. The exposed epitopes on a late antigen, VSG 78, of T.equiperdum were studied by the technique of monoclonal antibody (MAb) escape selection. MAbs that neutralize trypanosomes bearing VSG 78 reacted with the VSG only when it was attached to the trypanosome surface, suggesting that the most immunogenic surface epitopes are conformational. Trypanosome clones resistant to one of the MAbs yet still expressing VSG 78 or 78(20) were isolated in vitro. Two independent variants resistant to MAb H3 changed Ser192 to Arg by a single base change in the VSG gene and a variant resistant to MAb H21 had a single base change that converted Gln172 to Glu. A variant resistant to MAb H7 had several changes in the VSG gene, a gene conversion in the 5' region and an isolated mutation in codon 220 that is proposed to be responsible for the resistance phenotype. The isotypic bias of the MAbs against VSG 78 and an analysis of the natural variants that are resistant to MAb 78H21 suggest that glycosylation plays a role in the immunogenicity of these proteins. The analysis defines some of the exposed amino acid residues and demonstrates that VSG genes are altered by mutations and small gene conversions as well as replaced by large gene conversion-like events. The results provide biological data supporting the model of VSG structure obtained by crystallographic studies.